What’s Your Problem? Writing Effective Research Questions for Quality Publications - Purvis, Alison; Nicholas, Victoria; Tai, Joanna (Journal of University Teaching and Learning Practice, 2024)
Research questions play a central role in papers, indicating the phenomenon or problem that is being addressed, and clearly stating what is being investigated. Indeed, the presence of research questions within a research article is an established quality indicator, and research questions form the basis of determining hypotheses, methodology, methods, and how interpretations and analysis of outcomes are undertaken. Given the key purpose of a research article is to communicate the phenomenon or problem that is being addressed, research questions play a central role in clearly stating what is being investigated. The Journal of University Teaching and Learning Practice (JUTLP) seeks to publish high quality research papers which offer impactful guidance for teaching and learning practice in higher education. In this editorial, we explore what research questions are, how they are used, their key characteristics, different types of questions, and how to write them. We also make practical recommendations for authors, reviewers, and editors in how to use research questions, what to look out for when reviewing manuscripts and making decisions, and how to best support authors in producing quality publications by ensuring impactful research questions are included.